A Conceptual Analysis of the Integration of Panca Cinta into the Love-Based Curriculum at Pratama Widyalaya Educational Institutions - Ida Bagus Alit Arta Wiguna; I Gusti Komang Kembarawan; Sri Sofiana Amni; I Made Partha Wiguna (Widya Sundaram : Jurnal Pendidikan Seni Dan Budaya, 2026)
This research departs from the need to strengthen the Hindu early childhood education curriculum, which is not only oriented to academic achievements but also to character formation, spirituality, social concern, and ecological awareness. This article aims to conceptually analyze the integration of the Five Loves in the Love-Based Curriculum in Pratama Widyalaya. The Five Loves include Love for God, Love for Knowledge, Love for the Environment, Love for Self and Fellow Humans, and Love for the Homeland. This study uses a literature review method with a qualitative descriptive approach and content analysis. The sources of the study include love-based curriculum documents and Widyalaya regulations, as well as scientific articles related to character education, humanistic education, Hindu education, and early childhood education. The conceptual hypothesis of this study states that the integration of Panca Cinta can strengthen early childhood character education if these values are translated into learning objectives, play experiences, daily habits, educational unit culture, and evaluation of child development. The results of the study show that Panca Cinta serves as an integrative framework that brings together general education, Hindu distinctiveness, character education, and humanistic approaches. The contribution of this article lies in the preparation of a conceptual model of Panca Cinta integration that is specific to Pratama Widyalaya. These findings are important as the basis for the development of a religious, humanist, ecological, inclusive, and contextual Hindu early childhood curriculum.